2021
DOI: 10.1002/jcla.23742
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of tRF‐Pro‐CGG predicts poor prognosis in pancreatic ductal adenocarcinoma

Abstract: Background & Aims tRFs (tRNA‐derived RNA fragments) have been reported to facilitate cancer progression in multiple cancers. However, their role in pancreatic ductal adenocarcinoma (PDAC) remains to be determined. In this study, we mainly investigated the expression of tRF‐Pro‐CGG in pancreatic ductal adenocarcinoma and evaluated its relationship with the clinicopathology and survival time of patients. Methods 37 cases of pancreatic ductal adenocarcinoma, and 15 cases of normal pancreatic tissues were collecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Hence, a diagnostic tool with high sensitivity and specificity is urgently needed to remedy the deficiency of early diagnosis. 20 Recently, accumulating evidence has demonstrated tRFs serve as biomarkers in various cancer types, such as nonsmall cell lung cancer (NSCLC), 21 colorectal cancer (CRC), 22 gastric, 13,23 pancreatic, 24,25 breast, 26,27 ovarian 28 and prostate cancers. 29 Many studies have revealed alterations in the level of tRFs in various cancers, some of which are cancer type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, a diagnostic tool with high sensitivity and specificity is urgently needed to remedy the deficiency of early diagnosis. 20 Recently, accumulating evidence has demonstrated tRFs serve as biomarkers in various cancer types, such as nonsmall cell lung cancer (NSCLC), 21 colorectal cancer (CRC), 22 gastric, 13,23 pancreatic, 24,25 breast, 26,27 ovarian 28 and prostate cancers. 29 Many studies have revealed alterations in the level of tRFs in various cancers, some of which are cancer type-specific.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Li et al found that tRF-Pro-CGG was down-regulated in pancreatic ductal adenocarcinoma (PDAC) and was related to TNM stage and N stage. 81 Furthermore, a low level of tRF-Pro-CGG predicted poor prognosis and short overall survival (OS). 81 .…”
Section: Tsrnas In Cancersmentioning
confidence: 99%
“… 81 Furthermore, a low level of tRF-Pro-CGG predicted poor prognosis and short overall survival (OS). 81 .…”
Section: Tsrnas In Cancersmentioning
confidence: 99%
“…For example, tRNA-Ala-TGC-5-1 can be an indicator because it has more than 85% sensitivity and specificity in differentiating melanoma patients (Husna et al, 2022). The low expression of tRF-Pro-CGG betokens poor prognosis in pancreatic ductal adenocarcinoma (Li et al, 2021b). The circulated level of tRNA-Arg-CCT is impaired in patients with clear renal cell carcinoma compared to control (Zhao et al, 2018), likewise, Frontiers in Cell and Developmental Biology frontiersin.org in oral submucous fibrosis (OSF), tRF-Trp-CCA-007 is downregulated (Zeng et al, 2021).…”
Section: Knee Osteoarthritismentioning
confidence: 99%